1979
DOI: 10.1002/1097-0142(197901)43:1<162::aid-cncr2820430124>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Liposarcomas of the head and neck.A review of the literature and addition of four cases

Abstract: Liposarcomas of the head and neck are rare. There have been 25 previously reported patients in the literature. Four patients with head and neck liposarcomas, recently treated by the Head and Neck Surgery Service, Walter Reed Army Medical Center, are presented. Less than half of reported patients were noted to be living without evidence of disease. Prognosis generally corresponds to the cell type of the tumor. Intraoral, cheek and orbital tumors seem to have a worse prognosis compared to neck tumors. Wide local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…Well-differentiated liposarcoma is the most common subtype of all liposarcomas, recurring locally, but rarely metastasizing (16). Patients with this type of liposarcoma have an improved prognosis compared with those with other subtypes (17). Myxoid tumors, similar to the well-differentiated variety, are unlikely to metastasize and have a favorable five-year survival rate.…”
Section: Discussionmentioning
confidence: 98%
“…Well-differentiated liposarcoma is the most common subtype of all liposarcomas, recurring locally, but rarely metastasizing (16). Patients with this type of liposarcoma have an improved prognosis compared with those with other subtypes (17). Myxoid tumors, similar to the well-differentiated variety, are unlikely to metastasize and have a favorable five-year survival rate.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, Saunders et al. 3 suggested that palliative radiotherapy can enhance the survival ratio of cases with all types of non‐resectable liposarcomas. Also in the recent literature, it is reported that radiotherapy, particularly post‐operative adjuvant radiation, can be considered useful and might delay or prevent local recurrence 14–16 .…”
Section: Discussionmentioning
confidence: 99%
“…Liposarcoma represents approximately 1% of head and neck sarcomas, and their occurrence is rarely reported within head and neck [1][2][3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that the low-grade types are more sensitive to radiation than the high-grade types, although all types of liposarcoma are somewhat radiosensitive. 2,3 Saunders et al 8 have reported that palliative radiation therapy may prolong survival in unresectable tumors. Most studies do not recommend routine regional lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies do not recommend routine regional lymph node dissection. 6,8,9 No study has ever demonstrated conclusive evidence supporting chemotherapy in the treatment of liposarcoma. Wide and deep surgical excision, along with local radiation and/or chemotherapy, may be necessary for high-grade lesions.…”
Section: Discussionmentioning
confidence: 99%